EVENTOS ADVERSOS ASSOCIADOS A MEDICAMENTOS EM IDOSOS (Interdisciplinary Studies Journal, 2024)
The growing elderly population around the world requires changes in health services, especially pharmaceutical care. Elderly people consume many medications, increasing the risk of health interactions. This article sought to present reflections on drug interactions in the elderly and the impacts that these events have on their quality of life. An integrative literature review was carried out (2017-2022) in the LILACS, Medline, PubMed and SciELO databases. It is observed that the elderly, due to natural aging, have a higher prevalence of chronic diseases and suffer from a greater proportion of users of health services and, therefore, represent the age group most susceptible to the use of various medications and adverse events. use, and it is common to observe the presence of polypharmacy and frailty syndrome caused by medications, compromising the quality of life of these individuals. Thus, the study presented results related to adverse drug events in the health of the elderly, due to potential drug interactions related to polypharmacy that are common in individuals in this age group, highlighting the importance of strict control in the prescription and administration of medications to minimize the risks of interactions medication, involve improving the quality of life of the elderly.
Keywords: Elderly care; Iatrogenic; Adverse drug reactions in the elderly